Penerapan Pembelajaran Kooperatif Tipe Take and Give untuk Meningkatkan Hasil Belajar Kognitif Siswa Sekolah Dasar - Vicky Budi Utomo; Dedi Kuswandi; Saida Ulfa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
This study aims to improve the cognitive learning outcomes of fifth grade students of SDN Arjowilangun 04 Malang Regency in the academic year 2014/2015. This type of research is a classroom action research consisting of two cycles. Data collection techniques using observation, questionnaires, interviews, and tests. The results showed that there was an increase in student learning outcomes from cycle I to II using the take and give type of cooperative learning. This can be seen from the completeness of student learning outcomes in cycle I by 66% and increased to 93% in cycle II.